DESIGN OF THE INTEGRATED AUCTION SERVICE SYSTEM BASED ON SERVICE ORIENTED ARCHITECTURE FOR BUSINESS MODELS - Silvi Dwi Andrianti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2018)
This paper proposed a plan that SOA could be applied to conventional service change into IT service through a prototype design of the Integrated Auction Service System based on SOA for business models. The requirement analysis is proceeded by Unified Modelling Language and SOAML delivery strategy is selected the top-down strategy, service candidates and operations can be derived through analyzing detailed process of each use case, these can be abstracted at two service layers for effective implementation. Integrated Auction Service System was designed by WSDL, XML-based language and web-based programming language. By implementing ASP Visual C# to build dynamic web pages and database SQL Server is used to manage database. Testing process are Black Box and White Box testing unit.